Promoting parental education of infants hospitalized in a children's hospital in Tabriz, Iran: a best practice implementation project. Issue 3 (5th September 2021) - Kabiri, Neda; Hajebrahimi, Sakineh; Alizadeh, Gisoo; Azimzadeh, Solmaz; Dehkhoda, Nahid; Talebpour, Amin
ABSTRACT: Introduction: Parents of infants admitted to hospital have high information needs. A good educational program will improve the outcomes and communication needs of these parents. Results from some studies have shown that patient education in Iran is inappropriate and should be improved. Objectives: The aim of this evidence implementation project was to evaluate the current practice and implement the best practice related to promoting patient education in a children's hospital in Tabriz, Iran. Methods: A clinical audit was undertaken using the Joanna Briggs Institute Practical Application of Clinical Evidence System tool. Eight audit criteria that represent the best practice recommendations for patient education were used. A baseline audit was conducted followed by implementing multiple strategies, and the project was finalized with a follow-up audit to determine a change in practice. Results: Significant improvements in the follow-up audit in comparison with the baseline audit were as follows: evaluation of patient learning has been undertaken to determine met and unmet needs (from 65 to 77%); patients' learning needs, readiness to learn, and their learning style have been assessed before the implementation of an educational initiative (from 55 to 66%); and educational resources in different formats (e.g., written handouts, brochures, and links to online materials) are available in the ward (from 33 to 77%). Strategies that were implemented to achieve change in practice included conducting workshops and conferences, determining a trained nurse as responsible for educating parents, training in discharge time, the presentation of educational films daily, conducting group training, and installing related posters in the department and patient's room. The other five criteria were less compliant with best practice in the follow-up audit rather than the baseline audit; however, all of them except one (Criterion 3) were still up to 75% compliant, which is considered excellent by the audit team. Conclusion: The follow-up audit results indicated an improvement in providing parental education. It can be concluded that these interventions can facilitate the implementation of evidence into clinical practice.